An investigation of ventilation control strategies for louver windows in different climate zones. Issue 3 (8th December 2021) - Scheuring, Leonie; Weller, Bernhard
Abstract: Guaranteeing high indoor air quality and high degree of usersatisfaction at the same time is one of the challenges when improving the energy efficiency, namely the energy consumption, of a building. Current non-residential buildings mainly use mechanical ventilation systems to ensure high air quality. Natural ventilation can be an alternative regarding to lower maintenance costs and the psychological feeling of fresh air. Present natural ventilated buildings pose the risk of higher energy demand and less indoor air quality due to user's behaviour. Controlled natural ventilation based on indoor CO2 concentration and room air temperature is needed. However, the energy efficiency of a control strategy highly depends on climate zone and control parameters. This paper aims to explore the impact of different control strategies on the energy efficiency of an operable louver window. The analyses are done for yearly results and then for each month individual to clarify the effect of monthly varying control strategies. For the analysis EnergyPlus as a building energy simulation tool and for the natural ventilation in specific the EnergyPlus Design Flow Rate method is used. In the simulation four window opening strategies based on CO2 concentration and one simple intake/exhaust mechanical ventilation system were tested in Mediterranean, subtropical and moderate climate zone. The highest impact on energy efficiency and thermal comfort was seen at the cold months in the moderate climate. Long window opening strategies cannot be implemented because of a high thermal discomfort. In the hot months in the Mediterranean and subtropical climate an impact of ventilation strategies are seen as well. Only at moderate conditions no major differences in the natural ventilation strategies were observed. When comparing the natural ventilation conditions to mechanical ventilation major differences were found. In almost all climate conditions natural ventilation outperformed the mechanical ventilation. Only in winter months in the moderate climate mechanical ventilation outperforms natural ventilation.